2015
DOI: 10.1002/jmri.24895
|View full text |Cite
|
Sign up to set email alerts
|

Scan–rescan reproducibility of parallel transmission based amide proton transfer imaging of brain tumors

Abstract: Parallel transmission-based APT imaging of brain tumors showed good reproducibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 17 publications
5
55
0
Order By: Relevance
“…Since CEST imaging is highly sensitive to B0 inhomogeneity, shimming and correction for B0 inhomogeneity in the postprocessing are crucial. The accuracy and reproducibility of the APT imaging scheme used in the present study was confirmed in patients with various types of brain tumour [16].…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Since CEST imaging is highly sensitive to B0 inhomogeneity, shimming and correction for B0 inhomogeneity in the postprocessing are crucial. The accuracy and reproducibility of the APT imaging scheme used in the present study was confirmed in patients with various types of brain tumour [16].…”
Section: Discussionsupporting
confidence: 54%
“…This problem was solved in the present study by using the two amplifiers of a parallel transmission system in alternation [15,16], enabling 2 s of saturation at 100 % duty-cycle. A 2012 study showed that the APT contrast obtained with the 2-s saturation was higher than the corresponding values obtained with 0.5-s or 1-s saturation in various types of human brain tumours including gliomas [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this sequence only measured R 2 characteristics and could not correct for B 0 using phase information available via multiple gradient echoes. The fast EPI readout available using CEST‐SAGE‐EPI vastly improves acquisition times over slower, single‐slice, or volumetric approaches . Song et al and others have described single‐echo EPI approaches to speed up acquisition time; however, these studies lacked concurrent measurement of subsequent echoes that would allow for estimation of R 2 , normalR2*, normalR2 and B 0 .…”
Section: Discussionmentioning
confidence: 99%